Perancangan Rencana Strategis Teknologi Informasi di Pusat Teknologi Informasi dan Pangkalan Data UIN Suska Riau - Febrizal Alfarasy Syam (INTECOMS: Journal of Information Technology and Computer Science, 2018)
To support the vision of UIN Suska Riau, a Technical Implementing Unit in the field of computer and information system in UIN Suska Riau was established called the Computer Center (PUSKOM). However, in 2013, the Computer Center (PUSKOM) of UIN Suska Riau changed its name to the Information Technology and Database Center (PTIPD). The Center for Information Technology and Data (PTIPD) of UIN Suska Riau is a part that manages the use of information technology in the environment of Susin Riau UIN. PTIPD provides internet network services with a current bandwidth capacity of 200 Mbps. PTIPD also conducts training in information technology for students and lecturers and develops information systems and applications according to the needs of the UIN Susuka Riau academic community. Development of information systems that are not planned systematically will result in organizations not having a scale of priority in IS / IT development projects and seemingly patchy. The Center for Information Technology and Database (PTIPD) requires an appropriate strategic planning IS / IT, because if the IS / IT is not right both goals and objectives, then the IS / IT will not be a competitive advantage for the Center for Information and Database Technology (PTIPD) ) UIN Suska Riau. The form of Information Systems Strategic Planning that will be discussed in this study is to use the Ward and Peppard model, with input in the form of an analysis of the internal business environment and an analysis of the internal IS / IT environment. The results of this analysis will define the draft draft of the SI / IT strategy plan for the Information Technology and Database Center (PTIPD) of UIN Suska Riau. Keywords: IS / IT Strategic Planning, PTIPD, SI / IT Strategies, Ward and Peppard